Self-Assessment: Its Roles for Higher Education Students In Academic Writing Class - Cahyaning Fristiara (Hasanuddin University, 2018)
Self-Assessment is one kind of assessment technique that used by the teacher and conducted by the students in making grade of learning. By using this kind of assessment, students are stimulated to find strength and weakness in learning process, to assess the understanding about material given by the lecturer, and to judge the achievement in Academic writing class. This paper aimed to investigate the roles of self-assessment in Academic Writing Class. Purposive sampling used as sampling technique, where 5 students in Academic Writing Class involved as research sample. Self-assessment questionnaire applied in this research to know the roles of self-assessment in Academic Writing class. Interview also conducted in collecting some additional information regarding the student difficulties in conducting self-assessment. The result of the study showed that the use of self-assessment in Academic Writing class is important to know students strength and weakness in teaching and learning process, to increase the motivation in writing, and to improve the writing performance. This research expected to give contributions in the educational development especially encourages student’s awareness to optimize the use of self-assessment in Academic Writing Class and as consideration for the teachers in conducting assessment process in the teaching and learning activity.